Testicular size and sperm output in Holstein-Friesian and N'Dama bulls - Nwakalor, L.N.; Orji, B.I. (1983)
Correlation between testicular size and sperm output were investigated in N'Dama and Holstein-Friesian bulls. Records collected over a period of four months from October 1978 to January 1979 from 4 Holstein-Friesian and 4 N'Dama bulls were analysed. The means (± s.e.) of testicular measurements for Holstein-Friesian and N'Dama, respectively, were 35.6 ± 1.8 and 7.9 ± 0.3 cm. for scrotal circumference, 12.6 ± 0.3 and 7.7 ± 0.8 cm for testis length, 6.7 ± 0.3 and 3.7 ± 0.2 cm for testis diameter. Calculated mean testicular volumes were 296.8 ± 22.2 and 57.4 ± 10.1 ml respectively for Holstein-Friesian and N'Dama bulls. The mean total sperm per ejaculate were 8.80 ± 3.045 x109 for the Holstein-Friesian and 3.03 ± 0.905 x 109 for the N'Dama bulls. Simple correlations for Holstein-Friesian and N'Dama in the same order, were between body weight and scrotal circumference were 0.49 and 0.66, body weight and sperm output per ejaculate were 0.48 and 0.88, scrotal circumference and testicular volume were 0.74 and 0.60, scrotal circumference and sperm output per ejaculate 0.18 and 0.69, and testicular volume were -.45 and 0.84. Regression equations for predicting sperm output per ejaculate from testicular volume were given as Y = 13.458 - .031x and Y = -.650 + 0.038x, respectively, for Holstein-Freisian and N'Dama bulls.